2021
DOI: 10.5812/ans.112023
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovary Syndrome Can Lead to Neurocognitive Changes in Female Rats Treated with Letrozole

Abstract: Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder in premenopausal women. Brain functions may be affected in PCOS, and studies reported that PCOS patients are at greater risk for developing mental health conditions, including anxiety or depression. Objectives: This study was designed to evaluate the neurocognitive changes in letrozole-induced PCOS model. Methods: Twenty female Wistar rats (eight-week-old; 160 ± 10 g) were divided into two groups. Group one received vehicle only (carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…Furthermore, the loss of ability to experience pleasure (anhedonia), and anxiolytic behavior observed from the sucrose preference and elevated plus maze tests con rm overt depression in our model. These behavioral ndings in PCOS animals agree with other research works where similar cognitive and behavioral de cits in PCOS animals were reported (Yu et al 2016;Cui et al 2018;Mohammadi et al 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the loss of ability to experience pleasure (anhedonia), and anxiolytic behavior observed from the sucrose preference and elevated plus maze tests con rm overt depression in our model. These behavioral ndings in PCOS animals agree with other research works where similar cognitive and behavioral de cits in PCOS animals were reported (Yu et al 2016;Cui et al 2018;Mohammadi et al 2021).…”
Section: Discussionsupporting
confidence: 92%
“…PCOS is the most common gynecological endocrine disease which increases the body weight and the risk of type 2 diabetes mellitus and atherosclerosis (37,38). In agreement with our results, Mohammadi et al showed that ovaries develop histological changes after treatment with letrozole for 21 days and reported neurological impairment in rats with PCOS (24).…”
Section: Discussionsupporting
confidence: 92%
“…Our diagnosis of PCOS was based on biochemical evidence of sex hormonal dysfunction and hyperandrogenism, 26 , 27 in agreement with the Rotterdam criteria of 2003 (Rotterdam, 2003). 28 Our results showed that letrozole-only treated animals had significantly elevated serum GnRH, LH, and testosterone, and low FSH values.…”
Section: Discussionmentioning
confidence: 80%